Pengaruh Perhatian Orang Tua, Fasilitas Belajar, dan Kreativitas Guru Terhadap Keaktifan Siswa - Hartati, Tri; Pramusinto, Hengky (Universitas Negeri Semarang, 2021)
There are several factors that can affect student activity during the teaching and learning process. From preliminary observations found that SMK Karanganyar Wikarya does not yet have adequate facilities to support teaching and learning activities. The problem in this study is the level of student activity that is very low. The population in this study were all students of class XI Department of Office Administration Vocational School Wikarya Karanganyar which numbered 40 students. Researchers took a whole sample from the population because of the small population of 40 students. The variables in this study consisted of independent variables namely Parental Attention, Learning Facilities, Teacher Creativity while the dependent variable was Student Activity. Data collection method is done by Questionnaire / Questionnaire. The data analysis method uses regression analysis with SPSS tools. The results showed partially the parent's attention variable (X1) and teacher creativity (X3) did not significantly influence the student activeness variable (Y). while the Learning Facilities (X2) significantly influence the student activity variable (Y). The magnitude of R² variable parents' attention, learning facilities, and teacher creativity did not affect student activity, which was only 14.3% and the rest was influenced by other factors outside this study. Based on the results of research that has been done, the suggestion that can be given is SMK Karanganyar Wikarya should improve facilities to be more adequate.